2000
DOI: 10.1055/s-2000-7111
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Utility of Catalytic Fe(III)/Fe(II) Redox Cycling Towards Fused Heterocycles: A Facile Access to Substituted Benzimidazole, Bisbenzimidazole and Imidazopyridine Derivatives

Abstract: A catalytic Fe(III)/Fe(II) redox cycling approach has been examined and applied towards synthesis of a wide range of benzimidazole, bis-benzimidazole and imidazopyridine derivatives from oxidative coupling of aromatic ortho-diamines with aromatic as well as heterocyclic aldehydes bearing different types of substituents. This versatile and convenient method has further proven to be particularly useful in expeditiously affording a number of novel bisbenzimidazole class of Hoechst 33258 analogs towards potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(38 citation statements)
references
References 7 publications
(12 reference statements)
1
31
0
3
Order By: Relevance
“…Method a: 13 the appropriate diamino compounds and aldehydes were reacted in the presence of FeCl 3 /O 2 ; in one case (13), adding chloranil was found useful.…”
Section: Chemistrymentioning
confidence: 99%
“…Method a: 13 the appropriate diamino compounds and aldehydes were reacted in the presence of FeCl 3 /O 2 ; in one case (13), adding chloranil was found useful.…”
Section: Chemistrymentioning
confidence: 99%
“…NMR spectra of compounds 3d, 3e, 4f, and 7d showed that the introduction of the substituent (Cl or CH 3 ) at C-11 or N-1 position of benzimidazole fragment stabilized its form [17][18][19]. The carbon resonances of benzimidazole of benzene moiety became sharp.…”
Section: Resultsmentioning
confidence: 96%
“…Indeed, in most cases both methods gave only moderate or poor yields, probably as a consequence of the strong steric hindrance due to the bulky quinolizidine moiety. Preliminary attempts to form the benzimidazole nucleus by condensation of the diamino compounds 32 -36 either with aldehydes in the presence of FeCl 3 /O 2 [24], or with aldehyde -sodium bisulfite compounds [25], failed completely.…”
Section: Quinolizidinyl-benzimidazoles As Platelet-antiaggregating Agmentioning
confidence: 96%